A comprehensive systematic literature review of the burden of illness of Lennox–Gastaut syndrome on patients, caregivers, and society - Cross, J. Helen; Benítez, Arturo; Roth, Jeannine; Andrews, J. Scott; Shah, Drishti; Butcher, Emma; Jones, Aimee; Sullivan, Joseph (Epilepsia (Copenhagen), 2024)
Fully elucidating the burden that Lennox–Gastaut syndrome (LGS) places on individuals with the disease and their caregivers is critical to improving outcomes and quality of life (QoL). This systematic literature review evaluated the global burden of illness of LGS, including clinical symptom burden, care requirements, QoL, comorbidities, caregiver burden, economic burden, and treatment burden (PROSPERO ID: CRD42022317413). MEDLINE, Embase, and the Cochrane Library were searched for articles that met predetermined criteria. After screening 1442 deduplicated articles and supplementary manual searches, 113 articles were included for review. A high clinical symptom burden of LGS was identified, with high seizure frequency and nonseizure symptoms (including developmental delay and intellectual disability) leading to low QoL and substantial care requirements for individuals with LGS, with the latter including daily function assistance for mobility, eating, and toileting. Multiple comorbidities were identified, with intellectual disorders having the highest prevalence. Although based on few studies, a high caregiver burden was also identified, which was associated with physical problems (including fatigue and sleep disturbances), social isolation, poor mental health, and financial difficulties. Most economic analyses focused on the high direct costs of LGS, which arose predominantly from medically treated seizure events, inpatient costs, and medication requirements. Pharmacoresistance was common, and many individuals required polytherapy and treatment changes over time. Few studies focused on the humanistic burden. Quality concerns were noted for sample representativeness, disease and outcome measures, and reporting clarity. In summary, a high burden of LGS on individuals, caregivers, and health care systems was identified, which may be alleviated by reducing the clinical symptom burden. These findings highlight the need for a greater understanding of and better definitions for the broad spectrum of LGS symptoms and development of treatments to alleviate nonseizure symptoms.